2020
DOI: 10.1007/978-3-030-58150-3_37
|View full text |Cite
|
Sign up to set email alerts
|

Computational Complexity of Synchronization Under Regular Commutative Constraints

Abstract: The constrained synchronization problem (CSP) asks for a synchronizing word of a given input automaton contained in a regular set of constraints. It could be viewed as a special case of synchronization of a discrete event system under supervisory control. Here, we study the computational complexity of this problem for the class of sparse regular constraint languages. We give a new characterization of sparse regular sets, which equal the bounded regular sets, and derive a full classification of the computationa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Acknowledgement. I thank anonymous reviewers of the extended version (submitted) of [27], whose feedback influenced Section 3. I am also grateful to the reviewers of a previous version.…”
Section: S Hoffmannmentioning
confidence: 99%
“…Acknowledgement. I thank anonymous reviewers of the extended version (submitted) of [27], whose feedback influenced Section 3. I am also grateful to the reviewers of a previous version.…”
Section: S Hoffmannmentioning
confidence: 99%
“…It is natural to extend this result to other language classes, or even to give a complete classification of all the complexity classes that could arise. For commutative regular constraint languages, a full classification of the realizable complexities was given in [16]. In [17], it was shown that for polycyclic constraint languages, the problem is always in NP.…”
Section: Introductionmentioning
confidence: 99%
“…In [12] the result for two-state automata was generalized to arbitrary alphabets, and a complexity classification for special three-state constraint automata over a binary alphabet was given. As shown in [11], for regular commutative constraint languages, we only find constraint problems that are NP-complete, PSPACE-complete, or solvable in polynomial time. In all the mentioned work [8,11,12], it was noted that the constraint automata for which the corresponding constraint synchronization problem is NP-complete admit a special form, which we generalize in this work.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in [11], for regular commutative constraint languages, we only find constraint problems that are NP-complete, PSPACE-complete, or solvable in polynomial time. In all the mentioned work [8,11,12], it was noted that the constraint automata for which the corresponding constraint synchronization problem is NP-complete admit a special form, which we generalize in this work.…”
Section: Introductionmentioning
confidence: 99%